Lymphoid stromal cells - potential implications for the pathogenesis of CVID - Cousin, Victoria N.; Perez, Guillermo F.; Payne, Kathryn J.; Voll, Reinhard E.; Rizzi, Marta; Mueller, Christopher G.; Warnatz, Klaus (Frontiers in Immunology, 2023)
Non-hematopoietic lymphoid stromal cells (LSC) maintain lymph node architecture and form niches allowing the migration, activation, and survival of immune cells. Depending on their localization in the lymph node, these cells display heterogeneous properties and secrete various factors supporting the different activities of the adaptive immune response. LSCs participate in the transport of antigen from the afferent lymph as well as in its delivery into the T and B cell zones and organize cell migration via niche-specific chemokines. While marginal reticular cells (MRC) are equipped for initial B-cell priming and T zone reticular cells (TRC) provide the matrix for T cell-dendritic cell interactions within the paracortex, germinal centers (GC) only form when both T- and B cells successfully interact at the T-B border and migrate within the B-cell follicle containing the follicular dendritic cell (FDC) network. Unlike most other LSCs, FDCs are capable of presenting antigen via complement receptors to B cells, which then differentiate within this niche and in proximity to T follicular helper (TFH) cells into memory and plasma cells. LSCs are also implicated in maintenance of peripheral immune tolerance. In mice, TRCs induce the alternative induction of regulatory T cells instead of TFH cells by presenting tissue-restricted self-antigens to naïve CD4 T cells via MHC-II expression. This review explores potential implications of our current knowledge of LSC populations regarding the pathogenesis of humoral immunodeficiency and autoimmunity in patients with autoimmune disorders or common variable immunodeficiency (CVID), the most common form of primary immunodeficiency in humans.